Mitigation of the Javan Leopard (Panthera pardus melas Cuvier, 1809) Conflict in the Community of Tempur Village, Keling District, Jepara Regency - Aji, Danang Setyo; Santoso, Budi; Muali, Muali (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
A survey has been conducted to identify the conflict of the Javan Leopard (Phanthera pardus melas – P.p. melas) and its mitigation local wisdom in Tempur village, Keling District, Jepara Regency. The survey was conducted from July to October 2021. The survey was conducted through in-depth interviews with 15 selected respondents and questionnaires to 61 respondents at random in 6 hamlets in Tempur Village. The results of the interviews showed that there had been 17 times the P.p. conflict. melas that befell 2 hamlets from February to July 2021. The results of the questionnaire show that the Tempur Village community has always had a way of avoiding conflict with P.p. weld that is by means of; choosing the right time to go to the garden, not going to the garden/forest alone, doing good to others and the environment, obeying local community norms, always sharing when there is fortune and not disturbing the habitat of P.p. weld. In addition, the respondents also considered that P.p. Melas entering his village is not just a wildlife conflict, but also indirectly shows the victim's social behavior.